Fatores ambientais relacionados à ocorrência de cianobactérias potencialmente tóxicas no reservatório de Guarapiranga, SP, Brasil - dos Santos Machado, Leila [UNESP]; Santos, Larissa Gonçalves [UNESP]; Doval, Julio Cesar Lopez; Pompêo, Marcelo Luiz Martins; Moschini-Carlos, Viviane [UNESP] (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2016)
The objective of this study was to investigate which environmental variables are correlated to the occurrence and dominance of potentially toxic species in Guarapiranga Reservoir, in the metropolitan region of São Paulo/SP - Brazil. Water samples were collected in order to conduct physical, chemical and biologic analyses in the rainy and dry seasons in the reservoir’s upstream and intermediate zones and near its dam. The organisms were microscopically analyzed, identified and quantified, and their dimensions were measured for biomass calculation. The results indicated that the environmental characteristics of each zone of the reservoir are distinct and the biomass, as well as the occurrence of potentially toxic genera of cyanobacteria, vary according to these characteristics. The canonical correspondence analysis showed a correlation between high ammonium levels, low photic zone and neutral-alkaline pH with the biomass of Cylindrospermopsis raciborskii in the rainy season and of Planktolyngbya limnetica in the dry season in the intermediate zone of the reservoir (the Parelheiros zone). The high cyanobacteria biomass and water quality deterioration in the reservoir in the dry season have probably been influenced by the transposition of the Billings reservoir water over an extended period of the year, due to the intense drought of 2014.
Environmental factors related to the occurrence of potentially toxic cyanobacteria in guarapiranga reservoir, SP, Brazil
Keywords: Biomass; Eutrophication; Nutrients